1986
DOI: 10.1111/j.1600-0765.1986.tb01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival blood flow measured with a laser Doppler flowmeter

Abstract: Previous studies of gingival blood flow have used techniques that were discrete, invasive, or only applicable to animals. The present study assessed this parameter in 10 healthy humans using a noninvasive laser Doppler flowmeter (LDF). Blood flow rate was determined in the interdental papillae, free and attached gingiva, and alveolar mucosa. Measurements were made continuously at four sites per patient and discontinuously at 21 sites per arch representing the four locations. The effects of heat, cold, pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 21 publications
4
54
0
Order By: Relevance
“…In our study, we found the highest BF in the alveolar mucosa. Baab et al 9 showed that the laser Doppler flow wave pattern differed among free, interdental, and attached gingivae in humans; these findings correspond to those in this study. Baab et al 16 demonstrated that, in response to gingival cooling, patients with localized juvenile periodontitis and rapidly progressive periodontitis had significantly faster BF recovery curves than healthy control subjects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, we found the highest BF in the alveolar mucosa. Baab et al 9 showed that the laser Doppler flow wave pattern differed among free, interdental, and attached gingivae in humans; these findings correspond to those in this study. Baab et al 16 demonstrated that, in response to gingival cooling, patients with localized juvenile periodontitis and rapidly progressive periodontitis had significantly faster BF recovery curves than healthy control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Both heat and cold produced initial hyperemia, followed by a rapid return toward the baseline. 9 It has been shown experimentally that the average BF velocity through the larger vessels of the gingiva and periodontal ligament is faster than the flow of red blood cells in the dental pulp. 15 In our experiment, mean BF was significantly high (P < 0.01) in alveolar mucosa than in the gingiva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LDF emerged more than 30 years ago as a noninvasive and real-time method for perfusion measurements [66]. The LD technique made it possible to demonstrate that blood flow wave patterns differ consistently among gingival tissue types [67,68] and that there are no within-subject differences over time in LDFRs [16].…”
Section: Microcirculation Of the Gingivamentioning
confidence: 99%